2013
DOI: 10.1371/journal.pone.0062241
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Brain Derived Neurotropic Factors (BDNF) Delivery across the Blood-Brain Barrier for Neuro-Protection Using Magnetic Nano Carriers: An In-Vitro Study

Abstract: Parenteral use of drugs; such as opiates exert immunomodulatory effects and serve as a cofactor in the progression of HIV-1 infection, thereby potentiating HIV related neurotoxicity ultimately leading to progression of NeuroAIDS. Morphine exposure is known to induce apoptosis, down regulate cAMP response element-binding (CREB) expression and decrease in dendritic branching and spine density in cultured cells. Use of neuroprotective agent; brain derived neurotropic factor (BDNF), which protects neurons against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 68 publications
(77 reference statements)
3
77
0
Order By: Relevance
“…The percentage of transmigration of free MNPs or MNP-bound TIMP1 NF transmigration across the BBB is in the range of our previous studies. 43,56 We also did not observe neuronal cytotoxicity of the free TIMP1 (up to 1 µg), free MNPs (up to 20 µg), and MNPbound TIPM1 NF. In this study, surprisingly, we observed significantly reduced HIV infection in SK-N-MC cells in the presence of free TIMP1 and MNP-bound TIMP1 NF when compared with HIV controls.…”
mentioning
confidence: 61%
“…The percentage of transmigration of free MNPs or MNP-bound TIMP1 NF transmigration across the BBB is in the range of our previous studies. 43,56 We also did not observe neuronal cytotoxicity of the free TIMP1 (up to 1 µg), free MNPs (up to 20 µg), and MNPbound TIPM1 NF. In this study, surprisingly, we observed significantly reduced HIV infection in SK-N-MC cells in the presence of free TIMP1 and MNP-bound TIMP1 NF when compared with HIV controls.…”
mentioning
confidence: 61%
“…[22][23][24] A recent study has reported that MNP-bound BDNF can transmigrate across the blood brain barrier using an in vitro blood brain barrier model and subsequently exert the role of BDNF in neuroprotection, which represents an extensive application of MNPs with additional molecular factors. 25 In addition, chitosan and glycerophosphate are biodegradable, mucoadhesive, and nontoxic polymers, which show good biocompatibility for neuron survival and adherence. 26 Therefore, the magnetically responsive nanocomposites in the present study were made of chitosan, glycerophosphate, and MNPs.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of nanotechnology in nanomedicine has shown exciting prospects for the development of a novel drug delivery system to achieve the desired therapeutic levels of anti-HIV drugs and HIV-reactivating agents across the BBB. [18][19][20][21] In a nutshell, we need to deliver the drugs across the brain, activate the latent HIV, and subsequently release HIV drugs from the carrier at a constant rate for a longer period to increase therapeutic adherence and eradicate the activated HIV reservoir without hampering the integrity of the BBB. Considering these scenarios, we have developed a novel, nanoengineered layer-by-layer (LbL) assembly of an anti-HIV drug (tenofovir) and a latency-breaking agent (vorinostat) on ultrasmall magnetic nanoparticles (MNPs) to achieve the sustained release of the drug for 5-7 days.…”
Section: Introductionmentioning
confidence: 99%